Is the European Union a political union? An analysis of the policy area of freedom, security and justice - Mdladla, Gugulethu Delisile (My University, 2008)
ABSTRACT The purpose of this research report is to investigate whether the European Union has begun to take the form of a political union, both in terms of the policy areas it has expanded its activities into and the nature of this activity in these areas. It examines the decision-making, in particular, type, range and ramifications thereof, in the area of freedom, security and justice, which is a controversial and political policy area, in order to determine how pre-emptive the action emanating from the supranational is in relation to national governments. If the decisions are substantially pre-emptive, then it can be concluded that the European Union has gained authority and power in an important area and thus in general, has a political character and is in the process of becoming a political union.